Experimental autoimmune encephalomyelitis evolution was not modified by multiple infections with Strongyloides venezuelensis - Chiuso-Minicucci, F. [UNESP]; Bui Van, D. [UNESP]; Zorzella-Pezavento, S. F. G. [UNESP]; Peres, R. S. [UNESP]; Ishikawa, L. L. W. [UNESP]; Rosa, L. C. [UNESP]; Franca, T. G. D. [UNESP]; Turato, W. M.; Amarante, Alessandro Francisco Talamini do [UNESP]; Sartori, Alexandrina [UNESP] (Wiley-Blackwell, 2011)
P>According to the hygiene hypothesis, the increased incidence of allergic and autoimmune diseases in developed countries is mainly explained by the decreased contact between the human population and certain environmental agents as lactobacillus, mycobacteria and helminths. In this study, we evaluated the effect of multiple infections with Strongyloides venezuelensis on the development of experimental autoimmune encephalomyelitis (EAE) in Lewis rats. Multiple infections before EAE induction were not able to change the evolution of the disease. No alterations were observed in weight loss, clinical score and inflammation intensity at the central nervous system. The presence of significant levels of parasite-specific IgG1 but not IgG2b suggested a Th2 polarization. However, the percentage and absolute number of CD4+CD25+Foxp3+ T cells were not changed, being their levels in the spleen and lymph nodes of infected rats comparable to the ones found in normal animals. These results suggest that a Th2-polarized response without concomitant expansion of Foxp3+ regulatory T cells was not able to modify EAE progression. Even though these results do not threaten the hygiene hypothesis, they suggest that this paradigm might be an oversimplification. They also emphasize the need of a study to compare the immunoregulatory ability associated with different helminth spp.
Keywords: experimental autoimmune encephalomyelitis; hygiene hypothesis; Strongyloides venezuelensis